Responses of carabao' mango to 1-Methylcyclopropene in delaying ripening - Lacap, Angelyn T.; Bayogan, Emma Ruth V. (2019)
1-methylcyclopropene (1-MCP) is widely used to extend the postharvest life of various fruits and vegetables. The effect of 1-MCP in sachets was tested on ‘Carabao’ mango to delay its ripening. Mature green mangoes of uniform quality harvested at 105 d after flower induction were sanitized with 200 µL L⎺1 sodium hypochlorite, air-dried, and packed inside bamboo baskets (5-kg capacity) lined with newspaper, then treated with different concentrations of 1-MCP (0, 1, 10, 140µL L⎺1) in sachets. Once the 1-MCP sachet was placed in the center of the piled fruit, the bamboo basket was covered with five sheets of newspaper, secured with polypropylene twine and treated for 24 h under ambient room conditions. After treatment, the mangoes were stored in a cold room (19.0±1.2 ℃, 90.7±9.3% RH) and its quality was evaluated at two-day intervals for up to ten days. Weight loss, firmness, total soluble solids (sweetness), visual quality, stem-end rot, anthracnose, and peel color (using peel color index, L*, a*, b*, chroma, and hue angle) of the fruit were evaluated. Results showed that 140µ L L ⎺1-MCP was able to maintain firmness and sweetness of the fruit, indications of delayed ripening, until 2 and 5 d after treatment, respectively. In addition, mango fruit treated with 1-MCP also had better visual quality than untreated fruit. 1-MCP was not able to slow down the peel color changes in the fruit. 1-MCP was not able to slow down the peel color changes in the fruit but maintained the skin lightness (L*) until 5 d after treatment, particularly at 10µ L L⎺1 1-MCP. 1-MCP did not affect fruit weight loss and the onset of stem-end rot and anthracnose.
Keywords: Mindanao studies; Mango